Bioavailable iron production in airborne mineral dust: Controls by chemical composition and solar flux. (15th May 2019) - Hettiarachchi, Eshani; Reynolds, Richard L.; Goldstein, Harland L.; Moskowitz, Bruce; Rubasinghege, Gayan
Abstract: A large part of oceanic biological production is limited by the scarcity of dissolved iron. Mineral dust aerosol, processed under acidic atmospheric conditions, is the primary natural source of bioavailable iron to oceanic life. However, synergistic and antagonistic effects of non-Fe-containing minerals on atmospheric processing of Fe-containing minerals and Fe solubilization are poorly understood. The current study focuses on mineralogical influences of non-Fe-bearing semiconductor minerals, such as titanium dioxide (TiO2 ), on the dissolution of iron in selected natural mineral dust aerosols under atmospherically relevant conditions. Further, the role of elevated Ti concentrations in dust is evaluated using magnetite, a proxy for Fe(II) containing minerals, under both dark and light conditions. Our results highlight that relatively higher Ti:Fe ratios, regardless of their total Fe content, enhances the total iron dissolution in mineral dust aerosols as well as in magnetite. Moreover, elevated Ti percentages also yield high Fe(II) fractions in mineral dust systems under dark conditions. Upon irradiation however, dissolved Fe(II) is suppressed by high Ti levels due to the involvement of photochemical redox cycling reactions with hydroxyl radicals ( OH). These synergistic and antagonistic effects of Ti are further evaluated by altering the chemical composition of natural dusts with artificially added anatase (TiO2 ) and synthetic amorphous titania. The current study reveals important mineralogical controls by non-Fe-bearing minerals on dust iron dissolution to better understand global iron mobilization. Graphical abstract: Image 1 Highlights: TiO2 in natural mineral-dust enhances bioavailable iron production. TiO2 boosts dissolved Fe(II) fraction during night but suppress in daytime. Above effects of TiO2 persists with amorphous titania. Magnetite in dust decreases the Fe(II) production during the daytime.